Sound and visual landscapes as an educational resource for teacher training - Hurtado Soler, Amparo; Botella Nicolás, Ana María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The results of research on the didactic usefulness of the visual and sound landscape developed at the Teacher Training Faculty of the University of Valencia are shown. Following a mixed methodology with qualitative and quantitative questionnaires, the concept that future teachers have of agricultural landscapes and their possibilities as an educational resource is analysed. The sample consisted of 146 teachers in training for the Primary School Teacher Degree. The results show that sound and visual landscapes improve the understanding of natural phenomena from an interdisciplinary approach and promote the teachers’ competence development.